OP03 Effects of two years of liraglutide treatment on fatty liver disease in patients with type 2 diabetes: analysis of the Liraglutide Effect and Action in Diabetes-2 extension trial. (16th November 2010) - Armstrong, M; Falahati, A; Houlihan, D D; Elbrand, B; Schmidt, W E; Gough, S; Newsome, P N
Abstract : Introduction: Currently there are no established treatment options for fatty liver disease. Glucagon-like peptide 1 (GLP-1) analogues have been shown to reduce hepatic steatosis and markers of liver inflammation in rodents. Aim: To determine the efficacy of 2 years treatment with 1.8 mg liraglutide, a once-daily human GLP-1 analogue, on fatty liver disease and body composition in patients with poorly controlled type 2 diabetes (T2D). Method: Analysis was performed on the "Liraglutide Effect and Action in Diabetes-2" (LEAD-2) study cohort. LEAD-2 was a 26-week, double blind phase III trial with a 1.5-year open-label extension. Patients were randomised (2:2:2:2:1) to liraglutide 1.8, 1.2 or 0.6 mg/day, glimepiride 4 mg/day or placebo, all in combination with metformin 1.5–2 g/day. DEXA (n=160) and computerised tomography (CT) (n=154) sub-studies were performed to measure body fat composition and hepatic steatosis (defined by a liver-to-spleen attenuation ratio <1), respectively. Repeated measure and ANCOVA analysis was performed using last observation carried forward on the intention-to-treat population to estimate change from baseline. Values expressed as mean (SD). Results: 529/1091 patients (58% male; 87% white; age 56.7 years (9.5); body mass index 31 kg/m 2 (4.7); HbA1c 8.4% (0.9); male alanine aminotransferase (ALT) 32.0 IU/L (17.9); female ALT 27.3 IU/L (14.9)) completed 2 years treatment. Of the subjects enrolled in the sub-study 75% had the metabolic syndrome (ATP III classification) and 65.7 % (90/137) had hepatic steatosis on CT at baseline. Patients with elevated ALT levels (53%) at baseline (males >30, female >19 IU/L) had a significant reduction of ALT with liraglutide (−8.53 from baseline 40.9 IU/l, p<0.0001). This was a significant improvement vs glimepiride (p<0.05). 37% of patients normalised their ALT with liraglutide in comparison to 21% on glimepiride. Liver-to-spleen attenuation ratio significantly increased with liraglutide (+0.10, p<0.05) indicating reduced hepatic steatosis. Reductions in trunk fat tissue mass, trunk lean tissue mass and % total body fat with liraglutide were significantly different vs increases with glimepiride (−3.0 kg, −1.3 kg, −2.05%, respectively; p<0.05). Greater improvements were seen in liver-to-spleen attenuation ratio (+0.05), trunk fat mass (−1.6 kg) and % total body fat (−0.63%) with liraglutide vs placebo. Conclusion: Two years treatment with liraglutide significantly improves liver enzymes and hepatic steatosis in patients with T2D and associated fatty liver disease. Significant improvements in % body fat, in particular central adiposity support the role of liraglutide in reducing hepatic steatosis and cardiovascular morbidity.